Evaluating Sulfur-Composite Cathode Material with Lithiated Graphite Anode in Coin Cell and Pouch Cell Configuration - Uzakbaiuly, Berik; Mentbayeva, Almagul; Konarov, Aishuak; Kurmanbayeva, Indira; Zhang, Yongguang; Bakenov, Zhumabay (Frontiers in Energy Research, 2020)
High-performance sulfur-composite cathode material, sulfur/polyacrylonitrile/ketjen black, was prepared by simple mixing and low-temperature heat treatment route. The cell made of the composite cathode and anode from metallic lithium or lithiated graphite was assembled in coin cell configuration. Half-cells retained about 70% of their initial capacity of 1,270 mAh g−1 after 150 cycles, while full-cells retained about 85% of the initial capacity of 1,500 mAh g−1 for over 150 cycles. Since coin cells do not reflect the true performance of a practical cell, the cathode composite was assembled with lithiated graphite anode in a 45 × 85 × 6 mm3 pouch cell configuration. This cell retained about 81% of its initial capacity for over 100 cycles. At high cycling rates up to 1 C, the pouch cell demonstrated a moderate rate capability and exhibited good recovery and stable performance after high rate cycling. Also, the cell successfully passed safety tests such as overcharge, deep discharge, and mechanical short circuit tests.